Analisis Du Pont System terhadap Penilaian Kinerja Keuangan Industri Farmasi yang Terdaftar di Bursa Efek Indonesia - Yanti, Ni Putu Ayu Krisna Weda; Diatmika, I Putu Gede (Vokasi : Jurnal Riset Akuntansi, 2021)
Abstract The purpose of this study was to determine the financial performance of pharmaceutical companies using the Du Pont System. The method of analysis using the Du Pont System with variables namely Total Asset Turnover (TATO), Net Profit Margin (NPM), and Return On Investment (ROI). This research was conducted with a quantitative descriptive approach. The data used is secondary data in the form of financial statements, data collection techniques with literature study. The results of the study using the Du Pont System showed that one company with a Net Profit Margin variable that was above the industry average and seven companies with a Net Profit Margin variable that was below the industry average and Total Asset Turnover below the industry standard average below the industry standard. The financial performance of pharmaceutical companies during the 2019-2020 period has a value below industry standards it can be concluded that the company's efficiency in managing all assets to generate profits is not good enough. With one companies that generate a net profit and is declared good, but is not followed by the management of existing company assets. Keywords : Du Pont System, Return On Investment, Net Profit Margin, Total Asset Turnover